Brand Awareness Kampung Bali Di Kota Bekasi - Ni Gusti Ayu Ketut Kurniasari; Doddy Wihardi; Geri Suratno (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
The Kampung Bali in Bekasi City has now begun to be known for its characteristics and ornaments as well as a building style that is very thick with Balinese nuances. That is why, now Kampung Bali has begun to be visited by many local officials and journalists from online media and television to see firsthand the sustainable Balinese culture in Kampung Bali. This study suggests how the brand awareness efforts of Kampung Bali in Bekasi City are. This study uses a qualitative approach with a qualitative descriptive method. As the informants of this research are the residents who manage from the village of Bali. The results in this study suggest three things, namely where in an effort to establish brand awareness of Kampung Bali in Bekasi City through the preservation of Balinese culture which is carried out in daily activities. Furthermore, Kampung Bali also received support from the government in the form of a statement and also legality that explained that Kampung Bali was a tourist destination. The next thing to do is to use digital media in building brand awareness of Kampung Bali in Bekasi City.